Measurement of the neutron capture cross section of the fissile isotope 235U with the CERN n_TOF total absorption calorimeter and a fission tagging based on micromegas detectors - Balibrea-Correa J.; Mendoza E.; Cano-Ott D.; Krtička M.; Altstadt S.; Andrzejewski J.; Audouin L.; Bécares V.; Barbagallo M.; Bečvář F.; Belloni F.; Berthoumieux E.; et al. (EPJ Web of Conferences, 2017)
The accuracy on neutron capture cross section of fissile isotopes must be improved for the design of future nuclear systems such as Gen-IV reactors and Accelerator Driven Systems. The High Priority Request List of the Nuclear Energy Agency, which lists the most important nuclear data requirements, includes also the neutron capture cross sections of fissile isotopes such as 233,235U and 239,241Pu. A specific experimental setup has been used at the CERN n_TOF facility for the measurement of the neutron capture cross section of 235U by a set of micromegas fission detectors placed inside a segmented BaF2 Total Absorption Calorimeter.